2019
DOI: 10.1029/2019gl084951
|View full text |Cite
|
Sign up to set email alerts
|

Thermospheric Density Cells at High Latitudes as Observed by GOCE Satellite: Preliminary Results

Abstract: This study provides a climatological view of density cell structures at high latitudes in the lower thermosphere, using neutral mass density at 270 km derived from Gravity field and steady‐state Ocean Circulation Explorer (GOCE) satellite. Three types of the density cells named isolated low, isolated high, and wavy density cells are analyzed. Our results revealed that the density cell structures generally occur in the Northern Hemisphere and the local summer, but they are less frequently observed in the Southe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The heating‐induced thermospheric disturbances such as temperature and compositions propagate to lower latitudes mainly in the form of large‐scale circulations and TADs (Qian & Solomon, 2012). The asymmetric geomagnetic field could cause the asymmetric energy input and ionospheric convection in the two hemispheres, leading to LT‐dependent meridional winds and circulations (Crowley et al., 2006; Ercha et al., 2012; Weng et al., 2019; S. R. Zhang et al., 2015) via ion‐neutral coupling, which could be associated with the LT‐dependent hemispheric asymmetry of thermospheric density. The generation and propagation of TADs show LT dependence and hemispheric differences (Bruinsma & Forbes, 2007), which could be another reason for the LT‐dependent hemispheric asymmetry of thermospheric density.…”
Section: Discussionmentioning
confidence: 99%
“…The heating‐induced thermospheric disturbances such as temperature and compositions propagate to lower latitudes mainly in the form of large‐scale circulations and TADs (Qian & Solomon, 2012). The asymmetric geomagnetic field could cause the asymmetric energy input and ionospheric convection in the two hemispheres, leading to LT‐dependent meridional winds and circulations (Crowley et al., 2006; Ercha et al., 2012; Weng et al., 2019; S. R. Zhang et al., 2015) via ion‐neutral coupling, which could be associated with the LT‐dependent hemispheric asymmetry of thermospheric density. The generation and propagation of TADs show LT dependence and hemispheric differences (Bruinsma & Forbes, 2007), which could be another reason for the LT‐dependent hemispheric asymmetry of thermospheric density.…”
Section: Discussionmentioning
confidence: 99%
“…They suggest that the downward wind and ion drag‐driven force should lead to density depletion or a low density cell. Further,Weng LB et al (2019) invested the climatological view of density cell structures at high latitudes in the lower thermosphere, using neutral mass density at 270 km derived from the GOCE (Gravity Field and Steady‐State Ocean Circulation Explorer) satellite. They found that density cell structures in the lower thermosphere tend to occur in the local summer and the northern hemisphere, and that their local time distributions, horizontal scales, and relative magnitudes depend on the type of density cell structure.…”
Section: Ionospheric Dynamics and Couplingsmentioning
confidence: 99%